Drought-related media analysis from Andalusia and São Paulo. (15th March 2022) - Vargas Molina, Jesús; Paneque Salgado, Pilar; Augusto Breda Fontão, Pedro
ABSTRACT: Drought risk is a complex phenomenon that leads to different interpretations, public understanding of causes, consequences and adaptation strategies and, therefore, different responses. To date, and despite the rise of social media, mass media are still the main way through which society receives information about drought, mainly owing to accessibility and periodicity. Media content analysis can be useful not only for identifying the relevant stakeholders in debates about definition and management but also for monitoring the evolution of key issues over time. This work presents a methodology to systematise drought-related media content analysis. The methodology has been tested in two widely different case studies: The Autonomous Community of Andalusia in Spain and the Metropolitan Area of São Paulo in Brazil, which were recently exposed to drought. Results show that the methodology is applicable to different settings, regardless of the number of media outlets and the news stories analysed. The paper incidentally also shows the resistance to the paradigm shift in terms of drought management measures, where in both cases traditional measures based on increasing water availability continue to predominate over the measures of risk planning and mitigation.